TOWARD SUSTAINABLE COMBUSTION: A COMPREHENSIVE REVIEW OF NANOPARTICLE-INFUSED BIODIESEL - Ayam M. Alsaegh; Hussein Al-Gburi (Journals Park Publishing, 2025)
Using biodiesel as alternative fuel is a promising option due to its renewable source and favorable combustion qualities, but challenges such as lower calorific value, higher viscosity, poor cold-flow performance, and increased emissions limit its widespread adoption. Recent advances offer potential solutions: nanoparticles can act as catalysts during production and performance enhancers. Metal oxides and carbon-based nanomaterials improve transesterification efficiency, fuel atomization, ignition delay, and thermal conductivity resulting in higher brake thermal efficiency, lower brake-specific fuel consumption and reduced Emissions. The performance depends on optimal dosages (25–100 ppm), and excessive loading risks agglomeration, poor dispersion, or increased viscosity. Despite these results, many application remains limited by challenges related to nanoparticle stability, cost, toxicity, and regulatory approval. This review examines the mechanisms, performance influences, and limitations of nanoparticle-infused biodiesel. By addressing these issues, nanomaterial-enhanced biodiesel could become a viable next-generation fuel that balances performance and environmental concerns.
Keywords: Nanoparticle-infused biodiesel, Metal oxide nanoparticles, Carbon nanomaterials. Brake thermal efficiency, Emission reduction.